2010
DOI: 10.1115/1.4001290
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Palmitoyl Nanogold Particles on the Subzero Thermal Properties of Phosphate Buffered Saline Solutions

Abstract: Extensive studies document the effect of nanoparticles on thermal properties of fluids, such as thermal conductivity, although very few exist at subzero temperatures. The current study reports the effect of 1.4 nm palmitoyl nanogold particles (NPs) on the freezing properties of phosphate buffered saline solutions with the help of a differential scanning calorimeter. The results show that NPs have a complex effect on the two properties of interest, i.e., homogeneous nucleation temperature (Th) and phase change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…It has been reported that nanoparticles have a significant impact on the thermophysical processes/parameters of cryopreservation such as homogeneous nucleation, phase change temperature, the ice growth and devitrification temperature [6467]. Hydroxyapatite nanoparticles even can significantly improve the survival rate of in vitro matured porcine oocytes post-cryopreservation by vitrification [68].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that nanoparticles have a significant impact on the thermophysical processes/parameters of cryopreservation such as homogeneous nucleation, phase change temperature, the ice growth and devitrification temperature [6467]. Hydroxyapatite nanoparticles even can significantly improve the survival rate of in vitro matured porcine oocytes post-cryopreservation by vitrification [68].…”
Section: Resultsmentioning
confidence: 99%